BAP1 GERMLINE MUTATION WITH IRIDOCILIOCHOROIDAL MELANOMA AND MALIGNANT PERITONEAL MESOTHELIOMA. Issue Volume 16:Issues 2(2022) (31st December 2019) - Yaghy, Antonio; Lim, Li-Anne; Mashayekhi, Arman; Shields, Carol L.
Abstract : BAP1 tumor predisposition syndrome (BAP1-TPDS) is a novel cancer syndrome that can predispose patients to an increased risk of multiple rare cancers including choroidal melanoma and mesothelioma of the lung and peritoneum. Abstract : Purpose: BAP1 germline mutation can promote risk of uveal melanoma and mesothelioma. In this study, we report a patient with BAP1 germline mutation and uveal melanoma who developed a rare form of mesothelioma in the peritoneum. Method: Case report. Results: A 55-year-old white man noted blurred vision in the left eye. Examination revealed superotemporal episcleral sentinel vessels and a dark brown iris mass suspicious for melanoma, with angle invasion and involvement of the ciliochoroidal region. The tumor measured 14 mm in diameter and 10.3 mm in thickness. A diagnosis of iridociliochoroidal melanoma was rendered and plaque radiotherapy applied. Genetic testing revealed BAP1 germline mutation. At 3.5-year follow-up, tumor control was achieved, but radiation-related complications led to enucleation. At 5.5-year follow-up, incidental findings by laparoscopy revealed multiple peritoneal tumors, histopathologically proven to be malignant peritoneal mesothelioma. Lung evaluation was normal, and there was no melanoma-related or mesothelioma-related metastasis. Likewise, magnetic resonance imaging of the abdomen showed no evidence of hepatic metastasis. Conclusion: BAP1 tumor predisposition syndrome can promote risk of uveal melanoma and malignant peritoneal mesothelioma. Cancer screening for these malignancies is warranted.